Communicative strategy aimed at reducing exposure to arbovirus risk factors - María Ortíz Agui; Enit Ida Villar Carbajal; Marina Ivercia Llanos de Tarazona (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: The risk of exposure to the Aedes aegypti mosquito bite, arbovirus vector, may be reduced through communicative strategies that promote healthy attitudes and behaviors. Objective: to demonstrate the effectiveness of a communicative strategy aimed at reducing exposure to arbovirus risk factors. Methods: a quasi-experimental study was carried out, with a before and after design, for a sample of 65 schoolchildren from the Chinchavito town, department of Huánuco, Peru, in 2018. The study had four moments: diagnosis, preparation of the strategy, execution and evaluation. The information was obtained through a questionnaire and a scale. The main objective of the communicative strategy was to promote attitudes and behaviors to reduce exposure to arbovirus risk factors. Results: after applying the strategy, all the aspects evaluated showed an improvement, even if the differences with respect to the previous stage were statistically significant. Those that outstand the most in this regard were knowledge of the epidemiology of arbovirus (from 46% to 89%) and attitudes to comply with personal protection recommendations (from 18.5% to 84.6%). Conclusion: The communicative strategy applied is effective in the development of healthy attitudes and behaviors, which is evidenced in the higher scores obtained after the intervention.